Using a procedure doesn't mean following it: A cognitive systems approach to how a cockpit manages emergencies. (November 2016) - Carim, Guido C.; Saurin, Tarcisio A.; Havinga, Jop; Rae, Andrew; Dekker, Sidney W.A.; Henriqson, Éder
Abstract: The resources for action idea suggests that procedures, although they appear to be constraints that control, direct and restrict actions, are in fact resources that support a wide range of actions. Whereas the notion has gained considerable traction in the academic discourse, few empirical studies investigated how procedures are used as resources or if they are the only resources deployed. This paper applies resources for action approach to describe how a cockpit manages emergencies and other non-normal situations and the role played by the Quick Reference Handbook (QRH). Data was collected through participant observation, interviews, and analysis of technical documents. The results indicate that some situations encountered by pilots are far more complicated than the procedure anticipates. In order to cope with these situations, pilots employed strategies that interleaved a range of resources, often consulting fragments of the QRH checklists rather than following them from start to finish. These findings suggest that emergency checklists should be divided into smaller units that can be followed independently, and that procedures should sometimes provide pilots with choices rather than mandatory instructions. The other resources deployed can also enhance the performance of pilots.